ANALISIS BUSINESSES PROCESS IMPROVEMENT DAN PEMODELAN PELAPORAN CAR AUDIO PADA PT JAYA VICTORI CEMERLANG - Firianti; Awalludin, Dudi; Elanda, Anggi (P3M Politeknik Negeri Banjarmasin, 2022)
The company is seen as a collection of integrated processes and business processes become a strategic asset for a company to maintain its presence in the market. An organization generally has a goal to be able to survive and always increase its performance and productivity. Business processes that run within a company are one of the most important things for the company. PT. Jaya Victori Cemerlang is a trading company that distributes a variety of JVC Car Audio products, Panasonic Car Audio, and automotive components. Business processes that are running at the company today are still using the old method such as the delivery process, which in its management still uses paper media and still mentions one by serial number. Therefore this research aims to analyze business processes to determine the functional and non-functional requirements of the system which will then be modeled using the Unified Modeling Language (UML). In this study using the Business Process Improvement (BPI) approach to help improve the effectiveness and efficiency of business processes. The results of this study are a more effective and efficient system modeling of car audio reporting